Influence of relative user satisfaction and critical success factors on sustainability of climate change adaptation practices in Chamwino and Igunga, Tanzania - Baradyana, Edson N.; Kayunze, Kim A.; Ngowi, Edwin. E. (Frontiers in Climate, 2025)
Climate change impacts have driven initiatives like eco-village projects to implement Climate Change Adaptation (CCA) practices in vulnerable communities. However, their sustainability post-funding is uncertain. This study investigates how Relative User Satisfaction (RUS) and Critical Success Factors (CSF) influence CCA practice sustainability in Chamwino and Igunga agro-ecological zones, Tanzania. Using the Technology Acceptance Model (TAM) and Pinto’s Project Success Theory, we assessed RUS and CSFs’ comparative effects on sustainability. Data from 295 respondents implementing CCA practices were collected via using household surveys, Key Informant Interviews, and focus group discussion. Polychoric correlations, Multiple Correspondence Analysis, and multivariate ordered logit modeling evaluated sustainability (low, medium, high). Soil water conservation showed the highest sustainability (70.3%), followed by tree planting (66.3%), while energy-efficient cooking stoves had the lowest (48.7%). Strong correlations existed between soil water conservation, ox-drawn tillage, and tree planting (p < 0.001), with weaker correlations for energy-efficient stoves (p < 0.01). Perceived Image strongly influenced sustainability (β = 0.912–1.198, p < 0.001), especially for tree planting, followed by Accountability (β = 0.876–1.152, p < 0.001) and Transparency (β = 0.567–0.784, p < 0.01). Self-efficacy (β = 0.567–0.912, p < 0.05) and Usability (β = 0.645–0.812, p < 0.001) also impacted sustainability, while Individual Performance had minimal effect. CSFs like Self-efficacy, Perceived Image, Accountability, and Transparency increased sustainability probability by 16.5–19.4%. Low sustainability reflects social and governance barriers. RUS and CSF significantly influenced CCA practice sustainability, enhancing resilience through user perceptions and institutional support. Policymakers should integrate RUS and CSFs into CCA strategies, prioritizing community engagement, institutional support, and targeted interventions like subsidies and training to enhance post-funding sustainability. These findings highlight the critical role of user-focused governance in sustaining CCA practices long-term.